AB1068 CLINICAL FEATURES IN TURKISH CHILDREN WITH CHRONIC NON-BACTERIAL OSTEOMYELITIS. (June 2019) - Acarı, Ceyhun; Çomak, Elif; Çekiç, Şükrü; Turkucar, Serkan; Dundar, Hatice Adiguzel; Kılıç, Sara Şebnem; Akman, Sema; Unsal, Erbil
Abstract : Background: Chronic non-bacterial osteomyelitis (CNO) is a rare bone disease of autoinflammatory origin. CNO patients present with bone, joint pain and swelling. Other autoinflammatory disorders such as palmoplantar pustulosis, psoriasis and inflammatory bowel disease may accompany CNO. Objectives: Our aim is to determine demographic, clinical and radiological characteristics of Turkish children with CNO. Methods: Clinical, laboratory features and imaging findings were retrospectively analyzed in 28 CNO Turkish patients from three pediatric rheumatology centers. Clinical findings, radiological data, treatments and outcome were evaluated. Results: Of the 28 CNO patients, 10 (35.7%) female and 18 (64.3%) were male. Mean age at diagnosis was 9.54 (3-16.5) year. The lag time between symptoms and diagnosis was 6.5 (0-60) months. The median follow-up time was 18.5 (1-107) months. At the time of admission, symptoms were arthralgia (75.0%), bone pain (64.3%), limping (32.1%), swelling (28.6%), weakness (10.7%), and fever (3.6%). Two patients had inflammatory bowel disease (IBD) and six had familial Mediterranean fever (FMF). The bone lesions were mostly multifocal (%96.4), %3.6 was unifocal. The most frequently involved bones were femur (67.9%), tibia (53.6%) and pelvic bones (32.2%). (Table I ) The patients had mildly elevated CRP and ESH levels. HLA B27 association was 25%. ANA was positive in 5%. All patients were RF negative. Six patients had mutations in the MEFV gene, all of them had M694V allele. The most common finding in Histopathological examination (n=9) demonstrated sterile mixed cell infiltration composed of lymphocyte and neutrophils. MRI results were mostly defined as bone marrow edema, and bone scan findings showed increased osteoblastic activity. All of patients received NSAIDs. Other drugs were methotrexate (46.4%) sulfasalazine (39%), steroids (25%), anti-TNF drugs (32%), and pamidronate (25%). Response to treatment was partial in 32.1%, whereas 39.3% patients had complete remission. There was no response in 8 patients (28.6%). Conclusion: CNO was first described by Giedion in 1972 as multifocal bone lesions of inflammatory origin. 1 There are 500 CNO patients reported in the literature as individual or case series. 2 The laboratory findings are nonspecific and the diagnosis is mostly clinical and radiological. MRI and bone scan are the most commonly used imaging modalities. Histopathological results are non-specific, and may be necessary to exclude infection and malignancy. NSAIDs, sulfasalazine and methotrexate are mostly used in the treatment. Steroids, biological drugs and pamidronate are other options. There is still need for further treatment options, because there are significant number of resistant patients. References: [1] - Taddio A, Ferrara G, Insalaco A, Pardeo M, Gregori M, Finetti M, Pastore S, Tommasini A, Ventura A, Gattorno M. Dealing with Chronic Non-Bacterial Osteomyelitis: a practical approach Pediatric Rheumatology (2017) 15:87 [2] - Marion R. Roderick, Ethan S. Sen and Athimalaipet V. Ramanan Chronic recurrent multifocal osteomyelitis in children and adults: current understanding and areas for development Rheumatology, Volume 57, Issue 1, 1 January 2018, Pages 41–48 doi:10.1093/rheumatology/kex066 Disclosure of Interests: Ceyhun Acarı: None declared, Elif Çomak: None declared, Şükrü Çekiç: None declared, Serkan Turkucar: None declared, Hatice Adiguzel Dundar: None declared, Sara şebnem Kılıç: None declared, Sema Akman: None declared, Erbil Unsal Grant/research support from: Novartis, AbbVie, Roche, Koçak Pharma, Speakers bureau: Novartis, AbbVie, Roche, Koçak Pharma